Downregulation of miR‐491‐5p promotes gastric cancer metastasis by regulating SNAIL and FGFR4 - Yu, Ting (Cancer Sci, 2018)
Gastric cancer (GC) is among the most fatal cancers in China. MicroRNAs (miRNAs) are versatile regulators during GC development and progression. miR‐491‐5p has been demonstrated to act as a tumor suppressor in several types of cancer. However, the role of miR‐491‐5p in GC metastasis remains unknown. Here, we found that miR‐491‐5p was significantly decreased in GC tissues compared with adjacent non‐cancerous tissues, and low miR‐491‐5p level was associated with large tumor size. Overexpression of miR‐491‐5p significantly suppressed GC cell epithelial‐to‐mesenchymal transition (EMT) and tumor metastasis in vitro and in vivo. Mechanistically, SNAIL was identified as a direct target of miR‐491‐5p. The silencing of SNAIL phenocopied the tumor suppressive function of miR‐491‐5p, whereas re‐expression of SNAIL in GC cells rescued the EMT markers and cell migratory ability that were inhibited by miR‐491‐5p. In addition, miR‐491‐5p inhibited FGFR4 indirectly. Inhibition of FGFR4 also decreased the SNAIL level and impaired EMT and cell migration. Taken together, these findings indicate that downregulation of miR‐491‐5p promoted GC metastasis by inducing EMT via regulation of SNAIL and FGFR4.